Peningkatan Mutu Pengabdian melalui In-Tray Training di “Rumah Pengabdian” UIN Sunan Gunung Djati Bandung - Kusnawan, Aep; Muslimah, Sitta Resmiati; Salma, Fathya Zulva Fadlilah (LP2M of Institute for Research and Community Services - UIN Walisongo, 2022)
Efforts to improve the quality of community service are essential. Apart from the fact that community service is part of the Tri Dharma of Higher Education, it is also one of the measures for Higher Education regarding its existence in the community. Efforts to improve the quality of community service are now being pursued by the Center for Community Service (PkM) UIN Sunan Gunung Djati Bandung, among others, through the